Design of Dumbbell Shaped DGS-Notch Patch Antenna for Microwave Imaging System - Dayang Azra, Awang Mat; Chee, Ka Chin; Mohamad Nizam, Truna; Dyg Norkhairunnisa, Abang Zaidel; Shafrida, Sahrani; Kismet, Hong Ping; Kuryati, Kipli; Annie, Joseph; Kanaya, H. (Penerbit UTHM, 2020)
In this paper, square Microstrip Patch Antenna with notch is designed with dumbbell shaped DGS for microwave imaging system. The antenna is designed on dielectric substrate, FR-4 with relative permittivity, ℇ r = 4.7 and thickness, 1.6mm. The dumbbell shaped DGS act as the resonant structures and is placed as the ground layer of the antenna. Different location and size of dumbbell shaped DGS are simulated and analyzed. The result of return loss, radiation pattern and antenna gain are simulated using Electromagnetic Simulation Tools, fabricated and measured using Wave and Antenna Training System (WATS 2002). The design shows better performance with return loss of -38.99 dB and higher antenna gain of 6.20 dB compare to the conventional design, with return loss of -30.21 dB and antenna gain of 5.48 dB respectively.